A comparative study of DC/AC pure sine wave inverters - Bintu, Nusrat Khan; Muhammad, Labiba; Anjum, Navid (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electronics and Communication Engineering, 2013.